Pankrates: a Senior Statesman from Aphrodisias - Chaniotis, Angelos (Hyperboreus, 2017)
A new inscription from Aphrodisias (late ﬁrst century BCE or early ﬁrst century CE) contains an honoriﬁc decree and a grave epigram for Pankrates, member of a prominent Aphrodisian family and statesman. The decree seems to have been issued after he had served as στρατηγός τῆς πόλεως, but was inscribed on a stele later, after his death; the text mentions that a similar decree had been issued by Tabai. The epigram assimilates Pankrates’ life with a race, whose greatest, most important turning point, the καμπτήρ, is death. By referring to Pankrates’ public recognition and a life without sorrow, the poem offers consolation for his death.